2015
DOI: 10.1002/jnr.23700
|View full text |Cite
|
Sign up to set email alerts
|

Glycolytic metabolite methylglyoxal inhibits cold and menthol activation of the transient receptor potential melastatin type 8 channel

Abstract: Methylglyoxal (MG) is a reactive dicarbonyl compound involved in protein modifications linked to diabetes mellitus. The plasma level of MG is elevated in diabetic patients, particularly those with painful diabetic neuropathy. Diabetic neuropathy is often associated with spontaneous pain and altered thermal perception. This study assesses effects of MG on TRPM8, an ion channel involved in innocuous cold sensing and cold allodynia and also in cold-mediated analgesia. Acute treatment with MG inhibited the activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Cold allodynia refers to pain induced by a normally innocuous cold temperature, and is one of the main clinical symptoms experienced by patients undergoing chemotherapy. It can also occur in patients with other conditions such as diabetic neuropathy 13 , fibromyalgia, and traumatic neuropathy 11 . Cold hyperalgesia, in which a noxious stimulus results in a prolonged or intense pain response, commonly occurs with chronic inflammation 14 , such as in rheumatoid arthritis 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Cold allodynia refers to pain induced by a normally innocuous cold temperature, and is one of the main clinical symptoms experienced by patients undergoing chemotherapy. It can also occur in patients with other conditions such as diabetic neuropathy 13 , fibromyalgia, and traumatic neuropathy 11 . Cold hyperalgesia, in which a noxious stimulus results in a prolonged or intense pain response, commonly occurs with chronic inflammation 14 , such as in rheumatoid arthritis 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence suggests that TRPA1 is responsible for cold hypersensitivity in various rodent pain models. 27,4952 Although we cannot fully exclude the possibility of the involvement of TRP melastatin 8, a cold-sensitive TRP channel, 53,54 the present results showed that cold hypersensitivity is accompanied by TRPA1 sensitization in the early phase of STZ-induced DPN. Consistent with a previous finding, 53 the TRPA1 mRNA expression level in the DRG was not changed in STZ-induced diabetic mice in the present study, suggesting that the enhanced responsiveness of TRPA1 is caused by functional sensitization rather than by upregulation.…”
Section: Discussionmentioning
confidence: 50%
“…Previous studies have shown that MG, as a reactive byproduct of several metabolic pathways in cells, has been linked to painful neuropathies ( Bierhaus et al, 2012 ; Ciobanu et al, 2016 ; Barragan-Iglesias et al, 2019 ). Our previous study also showed that MG accumulation contributed to radicular leg pain in patients with LDH and the NP implantation-induced LDH rat model ( Liu et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%